2003
DOI: 10.2527/2003.811329x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea infusion and ruminal degradable protein concentration on microbial growth, digestibility, and fermentation in continuous culture1

Abstract: The effects of urea and rumen-degradable protein (RDP) on microbial growth, digestibility, and fermentation were examined using dual-flow continuous culture. The experimental design was a 4 x 4 Latin square with a 2 x 2 factorial arrangement of treatments. Factors were urea infusion (0.4 g/L of artificial saliva) and RDP concentration, and the treatments were as follows: 1) low RDP (8% of dietary dry matter) without urea (LDNU), 2) high RDP (11% of dietary dry matter) without urea (HDNU), 3) low RDP (8% of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
61
3
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 26 publications
17
61
3
8
Order By: Relevance
“…However, Ariza et al (2001) reported that EMS was greater for citrus pulp treatment than for hominy feed treatment. Supplementation of RDP tended to increase EMS in the present study, which is in agreement with results obtained by Griswold et al (2003).…”
Section: Rumen Effects Of Protein and Carbohydratesupporting
confidence: 83%
See 1 more Smart Citation
“…However, Ariza et al (2001) reported that EMS was greater for citrus pulp treatment than for hominy feed treatment. Supplementation of RDP tended to increase EMS in the present study, which is in agreement with results obtained by Griswold et al (2003).…”
Section: Rumen Effects Of Protein and Carbohydratesupporting
confidence: 83%
“…Supplementation of RDP significantly increased microbial N flow including LAM and SAM in the present study, which is in agreement with the continuous culture results obtained by Griswold et al (2003). Compared with starch, pectin produced similar microbial N to several previous studies (Strobel and Russell, 1986;Chester-Jones et al, 1991).…”
Section: Rumen Effects Of Protein and Carbohydratesupporting
confidence: 82%
“…However, the degradability of CP was not affected by diet, probably because the solubility of CP in grass silage and maize silage is similar (Givens and Rulquin, 2004). In addition, differences in the availability of N sources between diets were indicated by changes in iso-acid production (Griswold et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A shortage of rumendegradable feed protein (RDP) has been shown to reduce microbial digestion of carbohydrates (Griswold et al, 2003;Klevesahl et al, 2003), reduce synthesis of microbial protein (Martín-Orue et al, 2000;Griswold et al, 2003), decrease feed intake (Wheeler et al, 2002) and decrease weight gain of growing cattle (Zinn et al, 1994 and. A shortage of absorbed AA by cattle, either because of decreased synthesis of microbial protein or less than required intakes of rumen-undegraded protein (RUP), decreases weight gain of growing cattle (Lammers and Heinrichs, 2000).…”
Section: Introductionmentioning
confidence: 99%